PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SQUARE TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII MTsN TALAOK BAYANG KABUPATEN PESISIR SELATAN - Siska Media, Regina Gusye; Sudirman, Sudirman; Nerita, Siska (Pendidikan Biologi, 2014)
ABSTRACTÂ The studentsâ low learning achievement was regarded as one of the problems in the learning process. The students at MTsN Talaok Bayang had not yet been able to achieve the Minimum Standard score in Biology determined by school (70). One of the alternative ways to improve the studentsâ learning achievement was by applying Think Pair Square cooperative learning model. The aim of this research was to reveal the effect of using Think Pair Square cooperative learning model on Biology learning achievement of the students in class VIII of MTsN Talaok Bayang registered in Academic Year 2012/2013.This was an experimental research. The population of the research was all of students (214 students) inclass Â VIII Â of Â MTsN Â Talaok Â Bayang Â which Â were Â distributed Â to Â six Â classes. Â ByÂ  using Â purposive Â sampling technique, class VIII4 which consisted of 36 students was taken as the experimental group and class VIII5 which consisted of 35 students was chosen as the control group.The data obtained in this research was analyzed by using t-test. The result of the research indicated thatthe studentsâ average score in the experimental group (76,03) was higher than that of students in the control group (65,93). From the result of data analysis, it was figured out that the value of t calculated (4,22) was bigger than the value of ttable (1,67). This result signified that the hypothesis was accepted on the significance level 95% (Î± =0,05). Hence, it was concluded that the use of Think Pair Square cooperative learning model exerted an influenceupon Biology learning achievement of the students in class VIII of MTsN Talaok Kecamatan Bayang KabupatenPesisir Selatan.Â